Experimental study of canard UAV aerodynamics - Panayotov Hristian (MATEC Web of Conferences, 2017)
The present paper presents the aerodynamic characteristics of a canard fixed-wing unmanned aircraft TERES-02. A wind tunnel experiment is conducted using a specially designed model of the aircraft. The model is produced through the methods of rapid prototyping using a FDM 3D printer. Aerodynamic corrections are made and thorough analysis and discussion of the results is carried out. The obtained results can be used to determine the accuracy of numerical methods for analysis of aircraft performance.